Preparation and Photocatalytic Activity of TiO2/Fine Char for Removal of Rhodamine B. (2nd April 2015) - Ma, Mingjie; Guo, Weijie; Yang, Zhengpeng; Huang, Shanxiu; Wang, Guanyu
Abstract : TiO2 /fine char (FC) photocatalyst was prepared via sol-gel method with tetrabutyl titanate as the precursor and FC as the carrier. The structural property of TiO2 /FC photocatalyst was investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM), and the photocatalytic activity of TiO2 /FC was evaluated by photocatalytic degradation of rhodamine B (RhB) aqueous solution under UV light irradiation. The results showed that TiO2 was successfully coated on the surface of FC, and the TiO2 /FC photocatalyst had better photocatalytic efficiency and stability for degradation of RhB under UV light illumination as compared to that of the pure TiO2 and FC. The study provided a novel way for the application of FC to the photocatalytic degradation of organic wastes.